The Man Who Smiled - Mankell, Henning,Thompson, Laurie (New Press, The, 2012)
The New York Times called Henning Mankell that unusual thing: a European thriller writer whose work holds up as literature and who has broken out as an international phenomenon,
Description based on publisher supplied metadata and other sources
Keywords: Detectives; Sweden; Fiction; Electronic books